Evaluation of Efficiency of Accounting Information Systems: A Study on Mobile Telecommunication Companies in Bangladesh - Neogy , Taposh Kumar (Global Disclosure of Economics and Business, 2014)
The study evaluates the efficiency of Accounting Information Systems of the selected mobile telecommunication companies. The existing Accounting Information Systems which provide important sources of accounting information is viewed in the selected mobile telecommunication companies, more as the system for recording and reporting the business operations than as an information system for management decision making. Accounting Information Systems as a set of capital and human resources within an organization is responsible for the preparation of financial information and also of the information obtained from the collection and process of transaction data. The adequate accounting information is essential for taking every effective decision making process and adequate information is possible if the Accounting Information Systems run with efficiently. The efficient Accounting Information Systems is essential because it ensures that all levels of management get sufficient, adequate, relevant and true information for planning and controlling activities of the business organization. Accounting Information Systems cover a broad area in corporate world and produce quality information for the internal and external users to the business organization. The users of the Accounting Information Systems are satisfied about their systems. The study shows that the Accounting Information Systems of the selected mobile telecommunication companies are efficient since the examination of various indicators of efficiency showed favorable results and the responses of the surveyed respondents showed positive comments. JEL Classification Code: M41, D61